Management of Water Supply in the Cultivation of Different Agaricus bisporus Strains - Caitano, Cinthia Elen Cardoso [UNESP]; Vieira Júnior, Wagner Gonçalves [UNESP]; Soares, Douglas M. M.; Alves, Lucas da Silva [UNESP]; Nóbrega, Bianca de Barros; Pardo-Giménez, Arturo; Stevani, Cassius V.; Zied, Diego Cunha [UNESP] (MDPI, 2023)
The objective of this work was to evaluate the water supply method in the cultivation of button mushroom. The strains used were ABI 18/02, ABI 18/04, ABI 19/03, and ABI 11/19. An analysis of the ITS 1 + 2 regions, widely used as a fungal barcode, was performed in order to assess the genetics. The compost was packed in 35 × 50 cm plastic boxes with 10.5 kg m−2, and the inoculum was added (1% in relation to the compost weight). Before the addition of the casing layer, in half of the boxes, 25 L m−² of water was added directly to the colonized compost, resulting in the treatment of the water added to the compost. The yield, number, and weight of the mushrooms were analyzed. A phylogenetic tree for the A. bisporus strains based on ITS sequences confirms a close genetic relationship among the different collections of this species, and additional molecular markers are required to distinguish genotypes related to superior agronomic traits. The water management methods presented similar yields, except for one strain (ABI 18/04). The ABI 18/02 and 11/019 strains were more efficient when considering the method of adding water to the compost. This study suggests that the treatment of water added to the substrate is an alternative tool for reducing the application time and labor involved and as a control treatment to reduce water use.
Keywords: irrigation; ITS 1+2 regions; phylogenetic tree; yield